1998
DOI: 10.1038/sj.bmt.1701416
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tumor cells in peripheral blood samples from patients with germ cell tumors using immunocytochemical and reverse transcriptase-polymerase chain reaction techniques

Abstract: Summary:The aim of this study was to establish sensitive techniques for the detection of residual germ cell tumor cells in peripheral blood and progenitor cell harvests. For this purpose, we used immunocytochemical staining for cytokeratin filaments and reverse transcriptasepolymerase chain reaction (RT-PCR) for epidermal growth factor receptor (EGF-R) and germ cell alkaline phosphatase (GCAP). Germ cell tumor lines Tera-1 and Tera-2 were titrated into normal peripheral blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Therefore, these tumors present with very heterogeneous expression patterns of germ cell and epithelial cell-specific proteins. Not surprisingly, the only previously published immunocytochemical CTC analysis in patients with GCTs using the pan-anti-keratin antibody A45-B/B3 only identified 3 of 20 (15%) patients with advanced and/or relapsed GCTs as positive for CTCs (10). In our study, we performed an immunocytochemical analysis applying a combination of novel germ cellspecific (anti-SALL4, anti-OCT3/4) and epithelial cellspecific (anti-keratin, anti-EpCAM) antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these tumors present with very heterogeneous expression patterns of germ cell and epithelial cell-specific proteins. Not surprisingly, the only previously published immunocytochemical CTC analysis in patients with GCTs using the pan-anti-keratin antibody A45-B/B3 only identified 3 of 20 (15%) patients with advanced and/or relapsed GCTs as positive for CTCs (10). In our study, we performed an immunocytochemical analysis applying a combination of novel germ cellspecific (anti-SALL4, anti-OCT3/4) and epithelial cellspecific (anti-keratin, anti-EpCAM) antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These are the first 2 keratins expressed during mouse embryogenesis and might be expressed by seminomas and embryonal carcinomas (17)(18)(19)(20). Keratin 19 as a marker for epithelial cells was found to be present in some seminomas and the majority of nonseminomas (10). Furthermore, EpCAM is a homophilic, calcium-independent cell adhesion molecule and is uniquely expressed in germline and spermatogonial stem cells (21,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of these investigations, it became apparent that the detection of circulating tumor cells in PBPC by a reverse transcriptase polymerase chain reaction (RT-PCR) was associated with an increased relapse rate and an advanced tumor stage. In 1998, Hildebrandt et al [53] detected circulating tumor cells in autologous PBPC in TGCT patients by immunohistochemical and RT-PCR techniques.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Occult tumor cells in PBPC may directly contribute to relapse or may be an important predictor for rapid recurrence after myeloablative chemotherapy in patients with ovarian cancer. Several studies have recently shown that PBPC may contain residual tumor cells in hematologic malignancies (1–5) and some solid tumors (6–15). However, the issue of potential tumor contamination in the infused product has not been well studied in PBPC for patients with ovarian cancer.…”
mentioning
confidence: 99%